Assessing Students' Affinity for Technology on Learning Outcomes with Artificial Intelligence - Syangtan, Priyanka; Nath, Krishna; Budhathok, Rajan (International Journal of Atharva, 2024)
This study explores students' affinity for technology and its impact on learning outcomes with Artificial Intelligence (AI). Data from 123 students at Pokhara University were analyzed using a structured questionnaire with a 7-point Likert scale. The findings reveal a strong positive affinity for technology, with high mean scores indicating enjoyment in learning new technologies and staying current with tech trends. Participants also perceive AI as significantly enhancing their learning effectiveness, with mean scores reflecting positive impacts on learning outcomes. One-sample t-tests confirmed that both affinity for technology and AI's impact on learning are statistically significant, with p-values of 0.000. Despite the overall positive view of AI, a slight difference in mean scores suggests further investigation into additional factors affecting AI’s influence on learning outcomes. The study highlights the beneficial role of AI in education and emphasizes the need for ongoing research to optimize its integration into learning environments.